2003
DOI: 10.1021/ja029390a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Energetics of Single-Step Hole Transport in DNA Hairpins

Abstract: The dynamics of single-step hole transport processes have been investigated in a number of DNA conjugates possessing a stilbenedicarboxamide electron acceptor, a guanine primary donor, and several secondary donors. Rate constants for both forward and return hole transport between the primary and secondary donor are obtained from kinetic modeling of the nanosecond transient absorption decay profiles of the stilbene anion radical. The kinetic model requires that the hole be localized on either the primary or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
163
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(179 citation statements)
references
References 79 publications
(157 reference statements)
16
163
0
Order By: Relevance
“…Considering that the ionization potential of A is lower than that of T, the hole transfer for G-A-G sequence is expected to be faster than that for G-T-G sequence. Our results are in good agreement with the prediction, and similar results were reported in other photoinduced electron-transfer systems (26). In contrast, delocalization of a hole over several nucleobases may affect the holetransfer process (45).…”
Section: Direct Observation Of Hole-transfer Process Through Double-hsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering that the ionization potential of A is lower than that of T, the hole transfer for G-A-G sequence is expected to be faster than that for G-T-G sequence. Our results are in good agreement with the prediction, and similar results were reported in other photoinduced electron-transfer systems (26). In contrast, delocalization of a hole over several nucleobases may affect the holetransfer process (45).…”
Section: Direct Observation Of Hole-transfer Process Through Double-hsupporting
confidence: 93%
“…Lewis et al (15) and Wasielewski and coworkers (26) reported the kinetic study of single-step hole transfer in DNA by means of time-resolved transient absorption measurements. They determined the hole-transfer rate from G to GG by monitoring the decay of stilbene radical anion.…”
mentioning
confidence: 99%
“…It is clear from these data that a radical cation injected into the DNA condensate leads to the formation of lesions at nearby guanines that are detected as strand cleavage. Moreover, the GG steps that are closer to the AQ react more frequently than those located farther away, which is characteristic of those cases where hopping of the radical cation from one GG step to the next (k hop ) is slower than its trapping at a GG step by reaction with H 2 O or O 2 (k trap ) (22,(28)(29)(30). For the condensates, this distance dependence is rather steep, falling Ϸ10-fold over a distance of 70 Å.…”
Section: Resultsmentioning
confidence: 98%
“…21,22 By analyzing the detailed kinetics of electron transfer reactions, Lewis, Wasielewski and co-workers determined the rate constants of forward-and back-transfer from single G to a GG doublet and a GGG triplet. 23,24 The free energy values for these reversible hole transfer reactions are ~ − 0.052 V and −0.077 V, respectively. The rate constants for oxidation of isolated guanines vs. 5′-guanines in a GG sequence context was elucidated by Sistare et al using an electrochemical method.…”
Section: Introductionmentioning
confidence: 99%